Development of in-vitro bio-assay for The bioactivity determination of human Erythropoietin (rHuEPO) bio-pharmaceutical products (November 2020 - August 2021) - Lamia, Ayeasha Siddika (Brac University, 2022)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2021.